Հայ առաքելական եկեղեցու Վրաստանի և Իմերեթի թեմի Լոռվա գործակալությունը XIX դարի 30-ական թվականներին ֊ XX դարի առաջին տասնամյակում - Գրիգորյան, Վարդիթեր (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
The Lori district was one of the largest units of the Georgia-Imereti Diocese of the Armenian Apostolic Church. The number of villages within its boundaries exceeded 50 at the beginning of the 20th c. The Lori district was administered in the same way as the rest of the Diocese. The existing problems in the administrative structure of the Diocese were reflected here as well. Lori stood out among the other districts because some of the largest estates of the Diocese were located here.
Keywords: Պատմություն